Firm Value Creation through Major Channel Expansions: Evidence from an Event Study in the United States, Germany, and China. (May 2014) - Homburg, Christian; Vollmayr, Josef; Hahn, Alexander
Although changes to the channel system are among a firm's most critical decisions, prior research has neglected to examine the impact of channel expansions on firm value. This article investigates whether a firm's announcement of an increase in distribution intensity or the establishment of a new channel influences firm value. The authors also consider the moderating role of context-specific firm, market, and channel strategy contingencies. They test their hypotheses with an event study of 240 announcements of major channel expansions in the United States, Germany, and China. The results indicate that channel expansions affect firm value (i.e., through abnormal stock returns). However, the two types of channel expansions affect firm value differently. Whereas the establishment of a new channel positively influences firm value, reactions to an increase in distribution intensity are highly contingent. For example, firms operating in exceedingly turbulent or competitive markets experience firm value reductions in response to an increase in distribution intensity. Notably, the same two environmental contingencies enhance firm value when the firm establishes a new channel.